2017
DOI: 10.1123/ijspp.2016-0471
|View full text |Cite
|
Sign up to set email alerts
|

Telomere Length in Elite Athletes

Abstract: The results suggest that young elite athletes have longer telomeres than their inactive peers. Further research might assess the LTL of elite athletes of varying ages compared with both age-matched active and inactive individuals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
21
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 8 publications
5
21
0
1
Order By: Relevance
“…Our findings demonstrating that elite master sprinters have TL longer than their age-matched controls are in accordance with previous studies conducted with endurance athletes [8,21]. Muniesa, et al [21] reported that TL of elite endurance athletes was 16 % longer than the non-athlete counterparts.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Our findings demonstrating that elite master sprinters have TL longer than their age-matched controls are in accordance with previous studies conducted with endurance athletes [8,21]. Muniesa, et al [21] reported that TL of elite endurance athletes was 16 % longer than the non-athlete counterparts.…”
Section: Discussionsupporting
confidence: 93%
“…Our findings demonstrating that elite master sprinters have TL longer than their age-matched controls are in accordance with previous studies conducted with endurance athletes [8,21]. Muniesa, et al [21] reported that TL of elite endurance athletes was 16 % longer than the non-athlete counterparts. Similarly, Denham, et al [8] demonstrated that endurance athletes (aged between 18 and 55 years old) had TL 7.1 % longer in comparison to controls that were not engaged in a structured training.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Engagement in exercise is associated with longer telomeres and may slow down TL shortening [29]. Higher aerobic capacity is associated with longer leukocyte TL in endurance trained athletes [30][31][32] and young (18-32 yrs) [33] and older exercised-trained adults (55-72yrs) when compared to controls [34]. However, the literature regarding TL in skeletal muscle is conflicting, with only few studies reporting a positive association between higher levels of physical activity and longer telomeres in young and older healthy populations [35][36][37]; while other studies reported no association between skeletal muscle TL and exercise training levels [38,39].…”
Section: Introductionmentioning
confidence: 99%